2022
DOI: 10.1007/s00226-022-01400-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of combined thermal treatment and phenol–formaldehyde resin impregnation on the compressive stress of wood

Abstract: Understanding the effect of combined thermal treatment and phenol-formaldehyde resin impregnation on the compressive stress of wood. Wood Science and Technology, 56(4), pp.1071-1086.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These bonds can increase the stiffness and rigidity of the wood cell wall, making it more resistant to deformation and fracture. This is supported by Li et al [12], who found that thermal treatment promoted a chemical reaction between phenol-formaldehyde resin and wood, resulting in improved compressive stress.…”
Section: Table 1 Influence Of Temperature Modification and Duration M...mentioning
confidence: 61%
See 1 more Smart Citation
“…These bonds can increase the stiffness and rigidity of the wood cell wall, making it more resistant to deformation and fracture. This is supported by Li et al [12], who found that thermal treatment promoted a chemical reaction between phenol-formaldehyde resin and wood, resulting in improved compressive stress.…”
Section: Table 1 Influence Of Temperature Modification and Duration M...mentioning
confidence: 61%
“…However, our study also contradicts some other studies that reported a decrease in the compressive strength of wood perpendicular to the grain after thermal treatment. For example, Li et al [12] found that thermally treated spruce wood had lower compressive strength than untreated wood when the growth ring orientation was 40 degrees. This discrepancy may be due to the different wood species, growth ring orientations, thermal treatment conditions, and testing methods used in different studies.…”
Section: Table 1 Influence Of Temperature Modification and Duration M...mentioning
confidence: 99%
“…PF resins have different properties based on their M w and shape. As passive impregnation agents, it is important to evaluate the relationships among the penetration depths of PF resins, capacity of PF resins, and chemical and physical characteristics of the wood structure [34][35][36]. places into which PF resin can impregnate.…”
Section: Mechanism Underlying the Modification Of Beech Wood Via Pf R...mentioning
confidence: 99%
“…Such challenges require the development of various methods for processing and preserving wooden materials. Physical methods, such as chemical impregnation treatments and heat treatment, can improve the mechanical properties of wood and make it more resistant to biotic factors (Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%